Institutions, ownership structures, and distress resolution in China - Fan, Joseph P.H.; Huang, Jun; Zhu, Ning (Journal of Corporate Finance, 2013)
We investigate how institutional factors influence the behavior of distressed firms in emerging markets, where bankruptcy laws are often weak and debtors have greater bargaining power in distress. By studying two comprehensive samples of distressed firms in China, we find that local government quality and corporate ownership structure matter considerably to firm performance during distress. Distressed companies facing stronger institutional discipline and with greater private ownership have relatively better operating performance and are more likely to recover. Our results remain robust when we control for the endogeneity of entering distress, use different institutional proxies, and implement various definitions for distress.